Lo studio del populismo fra complessi e rimozioni - Marco Tarchi (Quaderni di Sociologia, 2020)
Used and abused by journalists and politicians, the concept of populism has always struggled to command respect in the scientific arena. The difficulties of defining its essence and circumscribing its range of applications have determined a contradictory destiny among political scientists, sociologists, philosophers and historians with sudden bursts of popularity and long periods of abandonment, interspersed with critical reinterpretations leaning towards scepticism. The electoral successes of populist parties and leaders in many countries since the late 1990s has revived the academic debate and fuelled a large amount of studies and research. This focus aims to detect and discuss some interesting contributions to the understanding of the features and causes of this phenomenon, that arise from the recent literature on the topic.